Quantifying Oxidized Lipids in Oven Fried and Deep Fried Potatoes: A Three-Way Analysis by LOI, Chemical Assays, and Lipidomics. (29th May 2020) - Williams, Traycie; Plummer, Paul; Blackburn, Mandy; Garrett, Timothy; Vasiliou, Vasilis; Koelmel, Jeremy; Penumetcha, Meera
Abstract: Objectives: Standard chemical methods that determine oxidized lipids in foods are laborious and require toxic chemicals. Our goal was to develop a mathematical lipid oxidation index (LOI) to predict oxidized lipid content of oven fried (OF) and deep fried (DF) potatoes and compare it to standard chemical assays and redox lipidomic analyses. Methods: We calculated the LOI value of each recipe using a mathematical formula which consisted of the parameters of 16 nutrients, time and temperature. Next, we OF and DF potatoes in soy, olive, and walnut oils and then extracted oil from the cooked potatoes using the modified Hara and Radin method. We assayed samples of each oil to quantify the conjugated diene (CD), conjugated triene (CT), peroxide (PV), acid (AV), and p-Anisidine (p-Ad) values. In addition, aliquots of each oil sample were sent to collaborators to determine the relative value of oxidized lipids by mass spectrometry and lipidomic informatics. Results: Overall, the chemical assays demonstrated that oven frying promoted significantly more oxidation than deep frying. Potatoes OF in walnut oil had greater mean CD (24.1 ± 0.44 vs 19.45 ± 0.06), CT (16.43 ± 0.25 vs 15.67 ± 0.12), AV (0.29 ± 0.01 vs 0.14 ± 0.003), PV (361 ± 7.6 vs 200 ± 6.06), and p-Ad (0.50 ± 0.03 vs 0.14 ± 0.01) when compared to DF potatoes ( P  ≤ 0.05). This increase in lipid oxidation was not consistent for potatoes prepared with soy and olive oils. LOI predicted a two-fold increase in lipid oxidation in OF potatoes as compared to DF potatoes no matter the type of oil (soy: 308 vs 150; olive: 319 vs; walnut: 330 vs 161). Finally, lipidomic analysis revealed a similar trend in the relative amounts of total oxidized lipids in OF potatoes (soy oil: 24% vs 12%; olive oil: 22% vs 7%; walnut oil 31% vs 17%) and was used to tentatively annotate over 3000 unique oxidized lipids. Conclusions: This preliminary study demonstrates that two of the three methods, LOI and lipidomic analysis, are in good agreement in quantifying lipid oxidation in OF and DF potatoes. However, the suboptimal agreement of the chemical assays suggests that the parameters of LOI require further examination. Funding Sources: MP is funded by a grant from the Research Dietetic Practice Group (RDPG)/Sugar Association. TW is funded by the Regina Myers McClain Foundation at UCM for his work as a research assistant.